Investigation of micro burner performance during porous media combustion for surface and submerged flames - Janvekar, Ayub Ahmed; Abdullah, M. Z.; Ahmad, Z. A.; Abas, Aizat; Hussien, Ahmed A.; S.Kataraki, Pramod; Mazlan Mohamed, Mazlan; Husin, Azmi; Fadzli, Khairil (2018)
Porous media combustion is considered to be one of the popular choice due to its tremendous advantages. Such type of combustion liberates not only super stable flame but also maintains emissions parameters below thresholds level. Present study incorporates reaction and preheat layer with discrete and foam type of materials respectively. Burner was made to run in ultra-lean mode. Optimum equivalence ratio was found out to be 0.7 for surface flame, while 0.6 during submerged flame condition. Maximum thermal efficiency was noted to be 81%. Finally, emissions parameters where recorded continuously to measure NOx and CO, which were under global limits.